Populism, ideology and contradiction: mapping young people's political views. Issue 2 (December 2015) - Pollock, Gary; Brock, Tom; Ellison, Mark
Abstract Forms of populism have long been a component of modern political discourse and systems where democracy relies upon popular legitimacy. There is, however, an uneasy relationship between some widely held views of 'the people' and the parties which seek to govern them. Contemporary academic and political discourse on populism often equates these views with right‐wing politics, whilst some radical scholars, suggest that these views, whilst controversial, are nonetheless examples of democratic expression. Using survey evidence from 14 European countries, we show that young people take up a mixture of political positions, some of which are strongly associated with indices of populism – cynicism, authoritarianism, nativism, xenophobia – others of which do not map neatly onto the typical 'left‐right' spectrum. We find evidence that some young people hold contradictory, often conflicting political viewpoints, which are reflective of the historical and cultural contexts of each location rather than of a 'populist' ideology. Where some theorists might use the term 'populism' pejoratively to denote a poorly and emotively grounded political ideology, we argue that this description denies its democratic legitimacy, as evidence suggests that young people draw on populist rhetoric to articulate views that are more reflective of local and regional concerns.